Images of Christ"s Saving Work in Ps.-Epiphanius" Homilies - Stander, Hennie (Hervormde teologiese studies, 1997)
Images of Christ's Saving Work in Ps.-Epiphanius' Homilies. One cannot really speak of a systematic theology on the subject of atone-ment in the patristic writers. Frances Young once said that 'it is in fact impossible to categorize neatly the thought of the major patristic writers on the subject of atonement'. She adds that one cannot do justice to the range of motifs and images that are found in describing the saving and atoning work of Christ if we merely dismember 'systematic theologies' to illustrate common soteriological themes. One can only appreciate patristic views of atonement if one begins by recognizing the multifaceted unity of imagery that pervades the literature. This then is the goal of this article: to discuss the rich images which Ps: -Epiphanius uses to describe the atoning work of Christ.